AB0606 Effects of 12-month etanercept or certolizumab pegol therapy on disease activity, bone turnover markers and peripheral qct bone mineral density in patients with rheumatoid arthritis. (23rd January 2014) - Váncsa, A.; Bhattoa, H. P.; Végh, E.; Gulyás, K.; Horváth, Á.; Pethö, Z.; Juhász, B.; Balázs, F.; Pogácsás, L.; Pál, I.; Szekanecz, Z.
Abstract : Background: Rheumatoid arthritis (RA) has been associated with secondary bone loss in the majority of patients. Biologics may have effects on generalized bone loss, however, less information has become available on etanercept (ETN) and certolizumab pegol (CZP). Objectives: In this study, we assessed the effects of anti-TNF treatment on inflammatory parameters, disease activity, bone turnover markers, bone mineral density (BMD) and radius quantitative CT (qCT) parameters in RA patients. Methods: Twenty-six RA patients (female:male=22:4) were treated with either ETN or CZP for 12 months. The mean disease duration was 9.7 years. Inflammatory parameters (ESR, CRP), disease activity (DAS28), autoantibodies, bone turnover markers (OC, CTX, P1NP), vitamin D3, lumbar spine and femoral DEXA, as well as radius qCT, a method capable of assessing total, trabecular and cortical density, were assessed at baseline and after 12 months of treatment with biologics. Results: DAS28 values improved significantly during the anti-TNFα therapy (5.06, 3.71, 3.10 and 2.90 mean DAS28 at baseline and after 3, 6 and 12 months, respectively). DEXA and bone markers showed no significant changes in BMD at the lumbar spine or femur region. Similarly, radius qCT revealed no significant changes in total density. However, peripheral qCT showed increased trabecular density after 12 months of anti-TNF therapy (BMD: 220 mg/cm 3 and T-score: +0.4) in comparison to baseline values (BMD: 203 mg/cm 3, T-score: -0.29). Conclusions: One-year anti-TNFα therapy using ETN or CZP may prevent further bone loss in RA. Biologic treatment may have beneficial effects ont he trabecular bone. Disclosure of Interest: None Declared